Fertility-sparing surgery for patients with stage IC2 or IC3 epithelial ovarian carcinoma: any evidence of safety?. Issue 2 (24th December 2021) - Nasioudis, Dimitrios; Heyward, Quetrell D; Ko, Emily M; Haggerty, Ashley F; Cory, Lori; Giuntoli II, Robert L; Kim, Sarah H; Latif, Nawar A
Abstract : Objective: Investigate the overall survival of patients with stage IC2/IC3 epithelial ovarian carcinoma undergoing fertility-sparing surgery. Methods: Patients aged < 45 years diagnosed between January 2004 and December 2015 with epithelial ovarian carcinoma, who underwent surgical staging and had tumor involving the ovarian surface (IC2), malignant ascites or positive cytology (IC3), were identified in the National Cancer Database. The fertility-sparing surgery group included patients who had preservation of the uterus and the contralateral ovary while the radical surgery group included patients who had hysterectomy with bilateral salpingo-oophorectomy. Overall survival was evaluated following generation of Kaplan–Meier curves while a Cox model was constructed to control for tumor grade and performance of lymphadenectomy. A systematic review of the literature was performed and cumulative relapse rate among patients with IC2/IC3 disease who underwent fertility-sparing surgery was calculated. Results: A total of 235 cases were identified; 105 (44.7%) patients underwent fertility-sparing surgery. There was no difference in overall survival between the fertility-sparing and radical surgery groups (p=0.37; 5- year overall survival rates 90.2% and 85%, respectively). After controlling for tumor grade and performance of lymphadenectomy, fertility-sparing surgery was not associated with worse overall survival (HR 1.22, 95% CI 0.56, 2.62). A systematic review identified 151 patients with stage IC2/IC3 disease who underwent fertility-sparing surgery. Cumulative relapse rate was 19.3% (n=29) while 12 (6.7%) deaths were reported. Median time to recurrence was 19 (range 1–128.5) months. Tumor recurrence involved the ovary exclusively in 42% (11/26) of patients, while 15% (4/26) had a lymph node, 35% (9/26) a pelvic/abdominal, and 8% (2/26) a distant tumor relapse. Conclusions: In a large cohort of patients with stage IC2/IC3 epithelial ovarian carcinoma, fertility-sparing surgery was not associated with worse overall survival. However, based on a literature review, relapse rate is approximately 20%.